2015
DOI: 10.1113/ep085129
|View full text |Cite
|
Sign up to set email alerts
|

Tracks through the genome to physiological events

Abstract: New Findings What is the topic of this review? We discuss tools available to access genome‐wide data sets that harbour cell‐specific, brain region‐specific and tissue‐specific information on exon usage for several species, including humans. In this Review, we demonstrate how to access this information in genome databases and its enormous value to physiology. What advances does it highlight? The sheer scale of protein diversity that is possible from complex genes, including those that encode voltage‐gated ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 62 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…1 B ) but it (and other conserved cell-specific alternatively spliced exons) can be resolved as a region of high conservation in multiple species alignments and conservation tracks (100 Vert Cons; Fig. 1 B ), and validated by analyses of mRNAs in specific cells and tissues (see below; Lipscombe et al, 2015 ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1 B ) but it (and other conserved cell-specific alternatively spliced exons) can be resolved as a region of high conservation in multiple species alignments and conservation tracks (100 Vert Cons; Fig. 1 B ), and validated by analyses of mRNAs in specific cells and tissues (see below; Lipscombe et al, 2015 ).…”
Section: Resultsmentioning
confidence: 94%
“…1 B ). E18a is an alternatively spliced cassette exon present in all mammalian Cacna1b genes but mRNAs containing this exon are frequently overlooked because e18a-Ca V 2.2 mRNAs are most abundant in regions of the nervous system that have poor representation in the RefSeq database ( Lipscombe et al, 2015 ; e.g., SCG ( Fig. 1 C ) and spinal cord; Gray et al, 2007 ), and they are found in low abundance in regions with strong representation in the RefSeq database (e.g., cortex, CT; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tools available to access the genome-wide data sets containing cell-specific information on exon usage that allow discrimination of proteins generated as splice isoforms are reviewed by Diana Lipscombe and colleagues. They show how such information has helped to establish the physiological significance of isoforms of genes encoding voltage-operated Ca 2+ channels and neuronal Na + channels, and discuss the potential of strategies to normalize splicing events associated with various diseases (Lipscombe et al 2015).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…They show how such information has helped to establish the physiological significance of isoforms of genes encoding voltage‐operated Ca 2+ channels and neuronal Na + channels, and discuss the potential of strategies to normalize splicing events associated with various diseases (Lipscombe et al . ).…”
mentioning
confidence: 97%